Diagnosis, treatment, and work impact of iron deficiency anemia in a Portuguese urban community. Issue 4 (17th July 2020) - Norton, Pedro; Araújo, Natália; Pinho, Paulo; Costa Gomes, Joana; Silva, Carla; Gama, Céline; Barbosa, Manuel; Ferreira, Pedro; Cunha, Sara; Moreira, Sara; Martins, Sílvia; Faria, Sofia; et al.
Abstract: Introduction: Little is known about iron deficiency anemia (IDA)'s treatment in Portugal. We aim to estimate the proportion of anemia, IDA, and iron deficiency without anemia; characterize the diagnostic procedures and prescription patterns; assess anemia's impact over work absenteeism, in a Local Health Unit. Material and methods: Cross-sectional study that evaluated complete blood counts, iron-containing prescriptions, comorbidities, economic failure, and disability certificates issued in 2015 at the Local Health Unit. Results: We evaluated 62, 794 complete blood count. The proportion of anemia was 16.5%, higher in patients with economic failure, pregnant women, and patients with congestive heart failure. Of the patients with anemia 87.8% had not serum iron and/or ferritin dosing, and of those with serum iron/ferritin levels tested 50.6% had IDA. IDA was higher in pregnant women, women aged ≥15 years and in patients with congestive heart failure. Approximately 56.2% of patients with IDA did not receive iron-containing medication, and in 38% of the cases the prescribed dose was subtherapeutic. Of the total iron prescriptions 44.1% were association therapies. Anemia accounted for 5.2% of the disability certificates issued in 2015 (1749 workdays lost). Discussion: Most patients with anemia are not being adequately evaluated and a major proportion does not undergo treatment or has subtherapeutic doses of iron. These results may explain the anemia's impact on work capacity. Conclusion: This is one of the largest studies on anemia in Portugal. An effort to adapt to the established recommendations is urged, to minimize the consequences of this disease.